Creating a Sustainable Constructionist Society with Generative Social Field (Constructionism Conference Proceedings, 2025)
Mitta Social Enterprise is an organization dedicated to expanding the impact of the Constructionism approach to education developed by Darunsikkhalai School for Innovative Learning. Currently, they are building upon this foundation by incorporating knowledge from Compassionate Systems. The DJOP Innovation 2023 project is one such initiative that implements Constructionism-based learning activities and cultivates Compassionate Systems thinking among participants. This is achieved through the creation of a generative social field for youth from 10 Juvenile Vocational Training Centers across the country. Findings from this project reveal that participants felt a sense of safety in the learning environment (Generative Social Field), which led to the realization that others valued them. This, in turn, fostered self-worth among the participants. They became more open to listening to their peers and actively shared ideas with one another. Additionally, they were able to reflect on their learning and connect the artifacts they created to their own life experiences. It is evident that Compassionate Systems enhances the reflection process inherent in Constructionism, making it more profound and connecting it to personal experiences and perspectives on life. This approach also fosters a friendly learning atmosphere, creating a sustainable learning community.